2015
DOI: 10.1080/03601277.2015.1065690
|View full text |Cite
|
Sign up to set email alerts
|

Learning from older citizens’ research groups

Abstract: This article adds to an ongoing conversation in gerontology about the importance of training and involving older people in research. Currently, the literature rarely distinguishes between the one

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Older people are usually bypassed by the mainstream participatory research community. Studies found that older people are willing to express themselves and contribute directly and proactively in the research process, which gives them the opportunity to continue their existing social roles Munn-Giddings et al, 2016). This approach also has the potential to challenge ageism and to access the views of older people, whose interests are often ignored or rejected and undervalued.…”
Section: Why Involve Older Adults As Peer Researchers?mentioning
confidence: 99%
See 2 more Smart Citations
“…Older people are usually bypassed by the mainstream participatory research community. Studies found that older people are willing to express themselves and contribute directly and proactively in the research process, which gives them the opportunity to continue their existing social roles Munn-Giddings et al, 2016). This approach also has the potential to challenge ageism and to access the views of older people, whose interests are often ignored or rejected and undervalued.…”
Section: Why Involve Older Adults As Peer Researchers?mentioning
confidence: 99%
“…As suggested by Walker (2007), "As a matter of human rights, older people have a right to be consulted about research that is being conducted on them." Enabling older people's engagement in research fosters their autonomy and active citizenship; their knowledge and ability is reconstructed in a process of understanding and empowerment (Munn-Giddings et al, 2016).…”
Section: Why Involve Older Adults As Peer Researchers?mentioning
confidence: 99%
See 1 more Smart Citation